Population Structure and Size of Early Yekaterinburg (1723-1744) - E. V. Borodina; S. I. Tsemenkova (Научный диалог)
The article is dedicated to the study of the social structure of the population of early Ekaterinburg. The main objective was to investigate individual social groups of the population, as well as the specifics of their formation in a situation of a rapidly growing and developing industrial and administrative center. The research was based on documentary sources of official record-keeping, the most significant of which were the data from local (factory) censuses of residents of the fortress factory in the 1720s — 1740s. Using quantitative analysis methods and social history approaches, the main social groups of the population were identified and characterized. Their numbers were determined, and the history of their formation and employment specifics in the mining industry were analyzed. The conclusions were drawn about the existence of a special social policy by the mining plant administration. It was found that it was aimed not only at maintaining optimal working capacity but also at progressively expanding the group of factory personnel by including representatives of new social groups such as soldiers, recruits, schoolchildren, exiles, and convicts in labor processes. It was shown that by the mid-18th century, Ekaterinburg, founded in 1723, was not inferior to both old and new urban centers in terms of infrastructure development, administrative, industrial, and social institutions, and population composition.